Immediate and mid-term results of implanting a MedInzh-2 mechanical prosthesis in the aortic position: ten-year experience of one center - S. T. Enginoev; A. A. Ziankou; I. I. Chernov; M. N. Dzhambieva; N. E. Ramazanova; D. Yu. Baev; M. M. Hassan; A. M. Bolurova; V. N. Kolesnikov (Креативная хирургия и онкология, 2024)
Introduction. MedInzh-2 is one of Russian mechanical prostheses. Although promising hemodynamic and hydrodynamic characteristics of this prosthesis are reported, only a few studies are available evaluating the implantation of this prosthesis in the aortic position and the maximum follow-up period in these studies does not exceed five years.Aim. To evaluate the immediate and long-term results of isolated aortic valve replacement with a MedInzh-2 mechanical prosthesis.Material and methods. The study included data collected from April 2009 to December 2019. During this period, 494 patients were implanted with a MedInzh-2 mechanical prosthesis in the aortic position at the Federal Center for Cardiovascular Surgery. The inclusion criteria were as follows: patient age of 18 years and older and implantation of a MedInzh-2 mechanical prosthesis in the aortic position. The exclusion criteria included the use of other types of mechanical prostheses and combined cardiac surgery. After applying inclusion and exclusion criteria, 224 patients were selected for the study. Th e median age of included patients was 55 (50–59) years. Among the patients who underwent surgery, the percentage of males amounted to 61.6 % (128 patients). The majority of patients (62.5 % or 140 people) were in NYHA class III–IV. Rhythm disturbance in the form of atrial fibrillation (AF) was observed in 11.6 % (26 patients). Th e median follow-up period was 48 (20–80) months.Results and discussion. In the early postoperative period, three patients died (1.3 %), and perioperative myocardial damage was recorded in 0.9% of cases. Permanent pacemakers were implanted in 2.7 % of cases. The frequency of stroke and acute kidney injury requiring hemodialysis amounted to 0.4 and 0.9 %, respectively. One-year, five-year, and ten-year patient survival rates were 98, 89, and 84 %, respectively. One year, five-year, and ten-year freedom from aortic valve reoperations were 100, 97, and 96 %, respectively. In addition, the ten-year freedom from prosthetic thrombosis reached 98 %.Conclusion. Th e clinical results and echocardiographic data obtained for the MedInzh-2 mechanical prosthesis implanted in the aortic position confirm its high efficacy in correcting aortic valve pathology.